(untitled) (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2020)
In national historiography the municipality of Corumbá and the Brazilian Army share the security and defense of the western border strip of the country. The strategic role of this city comes from its foundation on September 21, 1778. This period was the scene of land demarcation and territorial disputes between Portugal and Spain. However, by the end of the third decade of the nineteenth century, neighboring platinum countries (Argentina, Uruguay, and Paraguay) had already gained their independence. Until then, they were part of the Viceroyalty of the Silver, a Spanish possession. As a result, Corumbá has always stood out in Brazil’s different international relations with neighboring countries, decisively influencing the formation of border territoriality.